Some Disputed Issues Concerning Linguistic Points in English Language Instruction - Milal, A. Dzo'ul; Jannah, Raudlotul (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Despite its relatively consistent and definite subject, linguistics, particularly in its practical application within educational contexts, presents issues that may be disputed regarding language instruction practices, especially English Language Teaching (ELT) within Indonesian context. This paper focuses on the points of dispute, their sources, and potential solutions. As an argumentative article, the data were collected and analysed based on the reflective views of the writers. First, the disputes were described. Then, their sources were identified. Finally, solutions were suggested. It was revealed that the disputed points were related to tenses, sentence types, and question tags. Concerning the English tenses, the dispute is whether there are twelve or sixteen tenses in the English language. Related to sentence type, the debate is whether there is a nominal sentence in English. On the question tags, it is argued that question tag rules are vague and inconsistent. The sources of those debates mostly referred to interlanguage informational transfer and divergent approaches towards English language systems. After presenting a detailed description, the writers ultimately presented solutions to the disputes by the end of the paper.